2021
DOI: 10.1111/jfbc.13666
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol inhibited the metastatic behaviors of cisplatin‐resistant human oral cancer cells via phosphorylation of ERK/p‐38 and suppression of MMP‐2/9

Abstract: Cisplatin resistance is a major clinical problem in the clinical management of oral squamous cell carcinoma (OSCC) patients. Resveratrol is a natural phytoestrogen with antitumor activities. Whether resveratrol can overcome cisplatin resistance and prevent metastasis in OSCC cells is not known. In this study, we first examined the anti‐metastatic capacity of resveratrol and then explored the underlying mechanisms using a cisplatin‐resistant human OSCC cell line (CAR). The results demonstrated that at a non‐tox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
66
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(72 citation statements)
references
References 60 publications
(66 reference statements)
0
66
0
Order By: Relevance
“…It has been observed in our study that the MMP-9 immunoreactivities of RES and CONT groups were similar (p = 0,181). In the year of 2021, Chang et al (2021) have reported that applying 50 µM of Resveratrol for 24 hours causes a significant decrease in the MMP-9 expression of cancer cells Chang et al (2021). Likewise, in the year of 2016, Park et al, have shown that there was a significant decrease in the MMP-9 expressions of breast cancer cells when treated with 10 µM of resveratrol, that were loaded to pieces of gold, for 24 hours Park et al (2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been observed in our study that the MMP-9 immunoreactivities of RES and CONT groups were similar (p = 0,181). In the year of 2021, Chang et al (2021) have reported that applying 50 µM of Resveratrol for 24 hours causes a significant decrease in the MMP-9 expression of cancer cells Chang et al (2021). Likewise, in the year of 2016, Park et al, have shown that there was a significant decrease in the MMP-9 expressions of breast cancer cells when treated with 10 µM of resveratrol, that were loaded to pieces of gold, for 24 hours Park et al (2016).…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al (2019) and Xu et al (2017) have shown in their in vitro studies that in breast cancer and gastric cancer cells, resveratrol changes protein expressions that play a role in mesenchymal transition such as E-Cadherin and Vimentin Chen et al (2019), Xu et al (2017). Likewise, in the year of 2021, Chang et al, (2021) have reported that the application of 50 µM Resveratrol decreases the expression of MMP-9 protein in cancer cells Chang et al (2021). Boron, a trace element for organisms, has high affinity to oxygen and nature is filled with plenty of borates such as in the forms of boric acid and borax Devirian and Volpe (2003) .…”
Section: Introductionmentioning
confidence: 99%
“…Measurement of cell apoptosis. Cell apoptosis of HUVEC cells was examined as previously published (26,27). After drug treatments, HUVEC cells were ethanol-fixed and incubated with propidium iodide buffer for 30 min in the dark at 37˚C.…”
Section: Methodsmentioning
confidence: 99%
“…Intracellular ROS production. Intracellular ROS production was measured as previously described (26,27). After drug treatments, HUVEC cells were harvested, re-suspended in 10 μM DCFH-DA, incubated at 37˚C for 30 min, and analyzed by flow cytometry (BD Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…Prevention of EMT-like characteristics by RES has also been observed in CIS-resistant cancer cells. RES reduced the migration and invasive capacity of CIS-resistant CAR cells by inhibiting the phosphorylation of ERK and p-38MAPK as well as suppressing MMP2 and MMP9 expression [ 79 ]. Likewise, RES reversed CIS-induced snail expression by blocking the ERK pathway, thereby inhibiting the morphological changes and cell migration in ovarian cancer A2780 and A2780CP (resistant to CIS) cells [ 71 ].…”
Section: Biological Effects and Mechanisms Of Res In Acquired Drug-re...mentioning
confidence: 99%